1995
DOI: 10.1096/fasebj.9.7.7737456
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C and lipid signaling for sustained cellular responses

Abstract: Since the second messenger role was proposed for the products of inositol phospholipid hydrolysis, considerable progress has been made in our understanding of the biochemical mechanism of the intracellular signaling network. It is now becoming evident that stimulation of a cell surface receptor initiates a degradation cascade of various membrane lipid constituents. Many of their metabolites have potential to induce, intensify, and prolong the activation of protein kinase C that is needed for sustained cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,768
7
22

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,401 publications
(1,845 citation statements)
references
References 0 publications
48
1,768
7
22
Order By: Relevance
“…Once thought to be a single enzyme, PKC is now known to comprise a large family of enzymes with varying structure, cofactor requirements and function [101]. Its abundance and variation in both tissue and cellular distribution probably accounts for its participation in a vast array of signal transduction functions.…”
Section: Extracellular Signal-regulated Kinase Activation By G Proteimentioning
confidence: 99%
“…Once thought to be a single enzyme, PKC is now known to comprise a large family of enzymes with varying structure, cofactor requirements and function [101]. Its abundance and variation in both tissue and cellular distribution probably accounts for its participation in a vast array of signal transduction functions.…”
Section: Extracellular Signal-regulated Kinase Activation By G Proteimentioning
confidence: 99%
“…The calcium-dependent pathway regulates numerous cellular processes involving cell cycle, metabolism, and polarity in higher organisms (Berridge 1993). The activation of the calcium signalling cascade involves the interaction of ligands (growth factors and enzymes) with membrane surface receptors comprising heterotrimeric G proteins in the eukaryotic system (Nishizuka 1995). This association causes β-subunit dissociation from the complex and activation of membrane-bound protein phospholipase C. The rice blast genome encodes five phospholipase enzymes ( PLC 1, PLC 2, PLC 3, PLC 4 and PLC 5) that regulate conidiation, appressorium development and pathogenicity in M. oryzae (Choi et al 2011).…”
Section: Signal Transducing Cascades Associated With Appressorium Formentioning
confidence: 99%
“…Ever since the discovery of PKC extensive biochemical analyses has revealed a complex cascade of events that underlie enhanced and sustained activation of PKC (Nishizuka 1995), which is thought necessary to explain the putative role of this enzyme in persistent cellular changes associated with learning and memory processes. The search for the role of PKC in learning and memory, and especially a persistently active or autonomous form that makes the enzyme less dependent on second messengers and thereby prolonging its action well beyond the initial stimulating event, will continue.…”
Section: Resultsmentioning
confidence: 99%
“…Also in the mid-1980s, it was first demonstrated that several cis unsaturated fatty acids, produced from phospholipids by the action of phospholipase Az, were able to activate PKC providing a second pathway for PKC activation (McPhail et al, 1984;Murakami and Routtenberg, 1985). After these initial studies, many other cellular factors were found to modulate PKC activity, and the biochemical mechanisms underlying PKC activity have been shown to be rather complex (Nishizuka, 1995;Liu, 1996). These modulations contribute to the fine-tuning of PKC activity necessary to ensure regulated PKC activity in the midst of complex intracellular signaling pathways such as known to occur, for example, in learning and memory processes.…”
Section: The Discovery Of Additional Mechanisms Regulating Pkc Activitymentioning
confidence: 99%
See 1 more Smart Citation